Why Do We Eat? Determinants of the Attitude towards Eating in the Life Cycle Based on the Analysis of the Results of a Preliminary Survey - Ziółkowska, Beata; Mroczkowska, Dorota (INSTED: Interdisciplinary Studies in Education & Society, 2012)
It seems that eating means a simple satisfaction of a biological need ? hunger. However ? as proven by psychologists, sociologists and psychodieticians, etc., while eating certain foods or in specific circumstances we satisfy several other needs, including recognition, belonging, security, control, etc. The text presents results of a simple survey carried out in three groups different from one another in a development phase. As assumed it turned out that the needs which result from normative tasks and from needs of a development period are satisfied by the means of eating.